Multinodular goitre: a clinicopathological study from Kerala - Asokan, Meena; Cholakkal, Shanavas; Susheela, Bibilash Babu; Abdurahiman, Hima (International Surgery Journal, 2020)
Background: Multinodular goiter (MNG) occurs due to repeated hyperstimulation of thyroid gland due to iodine deficiency, goitrogens, antithyroid drugs and genetic defects. MNG can have different complications which include treacheal compression, retrosternal extension, malignancy and secondary thyrotoxicosis. The aim of the work was to study the clinical features and histopathology of MN in patients admitted for thyroidectomy in surgical wards of a tertiary care hospital in north Kerala. Methods: A prospective hospital based observational study in the patients in surgical wards of a tertiary care hospital in north Kerala from April 2011 to March 2012. The clinical data of patients who are subjected to thyroidectomy for MNG (clinical and fine needle aspiration cytology diagnosis) were included in this study. Patients undergoing completion thyroidectomy for recurrence or malignancy were excluded from this study. Results: MNG is more common in females. Female to male ratio 24:1 Majority are in the age group of 30-50 years (64%) with a mean age of 41 years. 38% (38 cases) had pressure symptoms in the form of dysphagia or dyspnea. Secondary thyrotoxicosis seen in 17% (17 cases). Fine needle aspiration cytology (FNAC) is not an error-proof investigation in MNG. 14 % of our patients had malignancy inspite of being reported as benign in FNAC. Among the malignancies papillary carcinoma thyroid was found to be most common accounting for 12% of cases (12/100) followed by follicular carcinoma. Conclusions: FNAC is not an error proof investigation in MNG. Incidental thyroid cancer in MNG is about 14 % with papillary carcinoma thyroid being the commonest.